Angiographic Severity of Coronary Artery Disease in Diabetic and Non-Diabetic Patients in a Tertiary Care Centre - Parvin, Tanjima; Haque, KMHS Sirajul; Siddique, Md Abu; Habib, SM Ahsan; Rahman, Mukhlesur; Rahman, Mohammad Hafizur; Sultan, Md Ashraf Uddin; Hoque, Md Harisul (University Heart Journal, 2015)
Objective: Diabetes mellitus, a common metabolic disorder, is often associated with severe coronary artery disease. In this study, we compared the angiographic severity of coronary artery disease in diabetic patients compared with that of non diabetic patients. Methods: This observational study comprised of 102 subjects who had coronary artery disease on coronary angiography in the Department of Cardiology, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, Bangladesh from January 2009 to December 2009. The patients were divided into two groups: one group with 24 (23.5%) diabetic patients and another group with 78 (76.5%) non diabetic patients. Demographic, clinical, laboratory and angiographic data were analyzed and compared between two groups. Results: Mean age±SD of the study subjects was 52.8±9.5 years and 94 (92%) of them were male. Diabetic patients were older (mean age±SD; 57.6±9.5 versus 51.3±9.9 years; p 004), and had higher frequency of hypertension (75% versus 50%, p 0.036), chronic stable angina (71% versus 41%, p 0.018), and lower frequency of smoking (42% versus 67%, p 0.034) and acute coronary syndrome (29% versus 59%; p 0.018) in comparison to non diabetic patients. Left main stem disease (21% versus 5%, p 0.031) and three-vessel disease (50% versus 31%, p 0.094) were more prevalent in diabetic patients. Severe coronary artery stenosis was significantly more present in diabetics than non diabetics (Gensini score, 50.9±29.9 versus 32.6±21.9, p 0.001). Conclusion: Diabetic patients are more likely to have severe and extensive coronary artery disease. Left main stem and triple vessel disease are more commonly seen in diabetic patients compared to non diabetic patients. University Heart Journal Vol. 10, No. 1, January 2014; 13-17